HEDONIS DALAM KARYA LUKIS - Cubindi Arofieqh; Yasrul Sami (Serupa The Journal of Art Education, 2020)
The purpose of making this final work is to visualize hedonism in Expressionist paintings and increase the ability to work in painting. The methods used in the work are the preparation, elaboration, synthesis, concept realization, and completion stages. So that ten works of hedonic visualization were created with the following titles: 1. "King", 2. "Party", 3. "Disco", 4. "Happy", 5. "Happy 2", 6. "Fancy" , 7. "Attitude", 8. "Attitude 2", 9. "Getting", 10. "How To".Kata kunci: hedonis, kehidupan, gaya hidup